(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
The article notes that during our independent development, the introduction of measures, legal framework and mechanisms to improve the activities of local authorities in all areas, the formation of a perfect legal framework for radical reforms in our country to ensure the full implementation of today’s goals. The Constitution, constitutional laws, codes and many other laws that form the legal basis of our socio-political life, as well as the structural subdivisions, the basis and principle of activity of local authorities were studied.